2020
DOI: 10.1021/acscatal.0c01963
|View full text |Cite
|
Sign up to set email alerts
|

The Role of Protons and Hydrides in the Catalytic Hydrogenolysis of Guaiacol at the Ruthenium Nanoparticle–Water Interface

Abstract: The mechanistic roles of free hydronium ions, surface hydrides, and interfacial protons during guaiacol hydrodeoxygenation (HDO) on ruthenium nanoparticles have been established. As guaiacol adsorbs on Ru, it loses its strong aromaticity and undergoes a rapid H-shift from its hydroxyl to meta carbons (in relation to its hydroxyl group), causing adsorbed enol and keto surface isomers to exist in chemical equilibrium. HDO occurs via a hydridic H-adatom (H*) attack on the enol, followed by a kinetically relevant … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
19
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 39 publications
(21 citation statements)
references
References 125 publications
2
19
0
Order By: Relevance
“…Water has been observed in previous studies to significantly affect the rate or selectivity of hydrogenation reactions; for example, water can decrease the magnitude of the enthalpy of adsorption of organic reactants 32 or provide new pathways for hydrogen/proton transfer. 33,34…”
Section: Rcf Of Poplarmentioning
confidence: 99%
“…Water has been observed in previous studies to significantly affect the rate or selectivity of hydrogenation reactions; for example, water can decrease the magnitude of the enthalpy of adsorption of organic reactants 32 or provide new pathways for hydrogen/proton transfer. 33,34…”
Section: Rcf Of Poplarmentioning
confidence: 99%
“…Platinum group metals and their sulfides are known to be effective catalysts for hydrodenitrogenation, , hydrodesulfurization, , and hydrodeoxygenation. Previous studies on simultaneous pyridine hydrodenitrogenation and thiophene hydrodesulfurization have shown that sulfided Pt/C and Pd/C catalysts exhibited higher HDN-to-HDS selectivities (up to an order of magnitude, 553 K) than sulfided Ru/C, Rh/C, NiMo/Al 2 O 3 , and CoMo/Al 2 O 3 catalysts . The pyridine HDN reactivities on Pt/C, Rh/C, Ru/C, Pd/C, NiMo/Al 2 O 3 , and CoMo/Al 2 O 3 catalysts decrease in the order of 12.3:7.5:4.5:4.0:1.3:1.0, which was ascribed to their different metal–sulfur binding energies and heats of bulk sulfide formation, , as these thermodynamic properties dictate the identities and electronic charges of the reactive hydrogen species, their catalytic involvements, and in turn rates.…”
Section: Introductionmentioning
confidence: 99%
“…Phenol would form its keto isomer in water and firstly hydrogenated to cyclohexanone (Ea 1 = 10.88 kJ mol −1 ), then cyclohexanone would be further hydrogenated to cyclohexanol (Ea 2 = 7.38 kJ mol −1 ). 24,37,41 Compared with the results reported for phenol hydrogenation in aqueous phase, Ru/SBA-15 gave a lower apparent activation energy in both of the two progress. 42,43 The zero-order character of phenol hydrogenation suggested the weak adsorption and fast desorption of the molecules reacted on Ru/SBA-15 catalyst, which explained high activity of hydrogenation and stability of the recycling reactions without carbon deposition on the catalyst.…”
Section: Resultsmentioning
confidence: 79%
“…[47][48][49][50] In addition, the absence of Brønsted acid sites on SBA-15 will lead to the inactivity for the dehydration of cyclohexanol and promote the hydrogenation of monophenols to stay in alcohols. 51 The cleavage of C aryl -OCH 3 was easier than C aryl O-CH 3 for the phenyl was a better electron attraction group compared with methyl for the C aryl -O-CH 3 ether bonds, 24 and the adsorption on Ru species could lower the activation energies of the C aryl -OCH 3 . 15 Similarly, C alkyl -OCH 3 was more difficult to cleavage compared with C aryl -OCH 3 for the steric hindrance and electronic effect will restrain the cleavage of C alkyl -OCH 3 bond and result in a higher temperature to achieve this process.…”
Section: Hydrogenation and Demethoxylation Of Methoxysubstituted Phenolsmentioning
confidence: 99%
See 1 more Smart Citation